DAYA TARIK WISATA BALIMAU KASAI DI KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Ria Zelfy Raini; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purposed to khow how balimau kasai tradition to be a tourist attraction in kampar sub-district and to know how about process of balimau kasai ceremony and also to identificate tourist atraction on balimau kasai activities in kampar sub-district. This research used descriptive qualitative method to analyze the problem And research subjects are those relating to balimau kasai and taken using purposive sampling and research techniques using observation interviews and documentation. Based on the research that has been done, Balimau Kasai has become a tradition carried one day before Ramadan, in the implementation of this ceremony there is an interesting thing, which is an herb used, makan bajambau, mengarak limau ke sungai Kampar, mandi balimau kasai. Balimau kasai become a tourism event to show decorative boat, folk festival, art show, and provide a souvenirs. Balimau kasai as a tourist attraction with uniquenees that can be seen by tourists such as people flocked to the river doing the ritual bath and look the interesting event to welcome the holy month of Ramadhan. Keywords : Tourist Attraction, Tourism Event, Ritual, Balimau Kasai, Kampar